Hand Perfusion in Patients with Physiological or Pathological Allen's Tests - Bartella, Alexander K.; Flick, Nina; Kamal, Mohammad; Steegmann, Julius; Kloss-Brandstätter, Anita; Teichmann, Jan; Hölzle, Frank; Lethaus, Bernd (Journal of Reconstructive Microsurgery, 2019)
Background The Allen test (AT) is a widely used clinical tool for the preoperative assessment of sufficient dual vessel hand perfusion although the impact of a pathological AT on tissue perfusion of the hand is not entirely clear. This study reveals perfusion changes of the hand in patients with pathological and physiological AT after terminating the dual blood supply.Methods Patients were distributed into 2 groups (physiological and pathological AT) that each contained 25 members. Perfusion of the thumb, middle, and small fingers was measured with a laser Doppler based (“oxygen-to-see” [O2C]) device. A steady state was measured and also values at 1, 3, 5, and 10 minutes after radial occlusion were measured.Results In patients with a physiological AT, only 1 out of 18 values differed significantly from the steady state measurements after 10 minutes, whereas patients with a pathological AT showed significant alterations in 8 out of 18 values. Oxygen saturation of the superficial and deep tissues appeared to be significantly worse in patients with a pathological AT.Conclusion Patients with a pathological AT suffered significantly more from the loss of dual hand perfusion than patients with a physiological AT. Patients with a pathological AT need more time to compensate for the altered perfusion pattern.
Keywords: Allen's test; radial free forearm flap; microsurgery